QUANTITATIVE AND QUALITATIVE ABDUCTIVE INQUIRY. - Bybee, Michael D. (Philosophy & Rhetoric)
The author comments on the article Two Models of Abductive Inquiry, by Brian Domino, which rightly suggests that an adequate account of abduction must consider the possibility that some predicates are qualitatively more important than others. Although I agree that abduction includes a qualitative component, I hesitate to abandon the quantitative component altogether, for granted that some predicates are more relevant, surely the greater the number of relevant predicates two objects share, the more persuasive the abduction. I also hesitate to adopt the clincher model that Domino provides. The claim that real inquirers cannot legitimately stop amassing abductive predicates at any point less than a perfect abduction apparently assumes that only certainty provides the legitimate basis for ending the collection of abductive predicates. The aim of inquiry, however, is not certainty but belief, that is, a level of confidence or comfort that a given proposition is true. Those with a greater need for certainty may well have to amass more or different predicates than those with a lesser need to achieve the threshold of belief, but all inquirers stop amassing predicates whenever they reach their level of confidence, whatever that may be and however they achieve it.